Zhodnocení firmy Areall, s.r.o. a návrh informačního systému - Vlach, Ondřej (Vysoké učení technické v Brně. Fakulta podnikatelská, 2016)
Práce je zaměřena na informační systém firmy Areall, s.r.o.. Cílem práce je zhodnotit současný stav IS a navrhnout změny, které by změnily veškeré požadavky vedení včetně ceny.

The work is focused on the information system of the company Areall, sro. The aim is to assess the current state of information systems and propose amendments that would change the management of all requirements, including price.
Evaluation Company Areall, Ltd. and Design of the Information System
Keywords: řešení IS pro malé podniky; informační systémy; podnikové informační systémy; solution for small companies; information systems; company information systems